A Critical Review of Mental Health Court Liaison Services in Australia: A first national survey. Issue 6 (1st November 2016) - Davidson, F.; Heffernan, E.; Greenberg, D.; Butler, T.; Burgess, P.
Abstract : Mental health Court Liaison Services have emerged in Australia as a key part of the response to the over-representation of people with mental illness in the criminal justice system. These specialist services aim to intervene early in the criminal justice process by identifying mentally ill individuals at the post-charge, pre-sentence stage, providing timely advice to courts and linkage with treatment providers. To date there has been no systematic comparison of the various models of court liaison in each of the Australian jurisdictions, and little is known about their effectiveness. This article presents the findings of the first national survey of Court Liaison Services. In the absence of clear national guidelines, services have formed independently of each other, shaped by the jurisdictional legislation and health services. While services were found to have similar aims, variation exists in their human resources, clinical processes, geographic coverage, and their ability to provide equitable access.